255 Musculoskeletal disorders and psychological comorbidity in Gulf War veterans and the relationship with physical and mental health and wellbeing. (11th October 2013) - Kelsall, L; McKenzie,; Roberts,; Forbes,; Urquhart,; Sim,
Abstract : Objective: To investigate musculoskeletal disorders, psychological comorbidity, and general physical and mental health and wellbeing in Gulf War veterans and a military comparison group. Methods: Cross-sectional study of 1456 male Australian 1990–1991 Gulf War veterans (veterans) and a non-Gulf comparison group (n = 1588). At a medical assessment in 2000–2002, reported doctor diagnosed arthritis or rheumatism, back or neck problems, joint problems, soft tissue disorders were rated by medical practitioners as non-medical, unlikely, possible, or probable diagnoses. Only musculoskeletal disorders rated as probable diagnoses were included in analyses. DSM-IV psychological disorders were measured using the Composite International Diagnostic Interview. Physical and mental health and wellbeing was assessed using the 12-item Short-Form Health Survey (SF-12). Results: Almost one-quarter of veterans (24.5%) and comparison group (22.4%) reported a musculoskeletal disorder (odds ratio OR 1.19; 95% CI 1.00–1.43). Having any or a specific musculoskeletal disorder was associated with depression and posttraumatic stress disorder (PTSD) but not alcohol use disorders. Physical health and wellbeing was poorer in those with a musculoskeletal disorder compared to those without (e.g., for veterans, difference in SF-12 PCS medians = -10.49: 95% CI -12.40, -8.57). Mental health and wellbeing was poorer in those with comorbid depression or PTSD compared to those with musculoskeletal disorders alone (e.g., for veterans, difference in SF-12 MCS medians = -20.74: 95% CI -24.3, -17.18). Similar patterns were found for the comparison group. Conclusions: Musculoskeletal disorders in the military were associated with depression and PTSD and poorer physical and mental health and wellbeing. Comorbidity of these conditions has implications for treatment and management and should be considered during assessment.